Studies of the Solvent-Free Knoevenagel Condensation over Commercial NiO compared with NiO Drived from Hydrotalcites - Hatem Layeb; Djamila Halliche; Nadia Aider; Baya Djebarri; Fouzia Touahra (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
In this study, we compared the effect of the commercial NiO, synthesis NiAl-HT and NiO-HT drived from hydrotalcite in Knoevenagel condensation reaction. The NiAl-HT sample was synthesized by the coprecipitation method with a molar ratio M2+/M3+ = 2 at constant basic pH. X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) were utilized to identify crystalline phases present in NiAl-HT, NiO-HT and commercial NiO. The chemical composition of the obtained solids was determined by Atomic Absorption Spectroscopy (AAS). Other techniques, such as Thermogravimetric Thermal Analyzer (TGA), Scanning Electron Microscopy (SEM) and Brunauere Emmette Teller Method (BET) were also used. As well as the BET showed the increase of the specific surface for the solid NiO-HT. The performance of the catalysts were studied in Knoevenagel condensation of benzaldehyde with ethyl acetoacetate without solvent to synthesis of organic compounds such as intermediates of dihydropyridines derivatives. The influence of different parameters, such as catalyst amount, reaction temperature and reaction time were optimized for studied the activity, the selectivity and the stability of the solids. Catalytic activity was in its lowest in the presence of NiAl-HT (26% of benzaldehyde conversion) whereas the benzaldehyde conversion increased to 77% in case of NiO-HT which can be explained by the presence of the basic sites of the NiO-HT oxides, a high surface area and a small crystallite size. Therefore, the lower increase in benzaldehyde conversion was noticed using commercial NiO (84%), perhaps owing to its high purity. A reaction mechanism is proposed by using density functional method (DFT). Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)